Finance and Efficiency: Do Bank Branching Regulations Matter? - Acharya, Viral V.; Imbs, Jean; Sturgess, Jason (Review of Finance, 2011)
Abstract We document that the deregulation of bank branching restrictions in the United States triggered a reallocation across sectors, with end effects on state-level volatility. The change cannot be explained simply by shifts in sector-level returns and volatility. A reallocation effect is at play, which we study in the context of mean-variance portfolio theory applied to sectoral returns. We find the reallocation is particularly strong in sectors characterized by young, small and external finance dependent firms, and for states that have a larger share of such sectors. The findings suggest that improving bank access to branching affects the sectoral specialization of output, in a manner that depends on the variance-covariance properties of sectoral returns, rather than on their average only.